Potential analysis of palm sugar industry development in Lombo Village, Sidrap District. Issue 1 (November 2021) - Fitriwati,; Syahidah,; Makkarennu,; Syahid, M; Syahwiah, A
Abstract: Palm sugar is one of the primary commodities in agribusiness sector, that have a huge potential to be developed into an industry. The palm sugar industry has an important role in employment, income distribution, and improving the welfare of local communities. The problem in this research is how to develop the potential of small palm sugar industry in Lombo Village, Sidrap Districts. The purpose of this study is to identify external and internal factors, 2. Formulate the palm sugar industry development strategy. The method used in this research is descriptive with a qualitative approach. The sampling method in this study used the accidental sampling method with a selected sample of 15 respondents. Data analysis was performed using SWOT matrix analysis. The conclusions obtained are based on matrix analysis of Internal Strategic Factors (IFAS) 2.9 and External Strategic Factors (EFAS) 2.4. This shows that the palm sugar industry in Lombo Village, Sidrap Districts has strengths that can be maintained or improved and have opportunities that can be developed. The development strategy that can be carried out is a strategy that supports aggressive growth. The advice given is to maintain the characteristic taste of the product and improve product quality by creating innovations in product packaging, diversifying product types so that they have high added value.